ANALISIS KEMAMPUAN REPRESENTASI GAMBAR DAN MATEMATIS MATERI GERAK LURUS PADA SISWA SMA DI BONDOWOSO - Adinda Della Widya Asiska; I Ketut Mahardika; Singgih Bektiarso (Universitas Jember, 2021)
Multirepresentation is a learning approach that provides information in various forms to make it easier for students to understand learning materials in the form of diverse representasion. This study aims to analyze the ability of image representation and mathematical representation of students.Respondents to this study were 3 schools in Bondowoso district, namely SMAN 1 TENGGARANG, SMAN 1 TAPEN, and SMAN 3 BONDOWOSO.Purposive sampling area method is a method used to determine the place of research.The data collection method in this study uses tests, interviews, and documentation.The test instrument consists of 5 questions containing aspects of image and mathematical representation.The test results are data on the ability to represent images and mathematically as well as classification of student ability categories presented in percentage form.The multirepresentation capability category is divided into 4 categories, namely very good, good, enough, less, and very less.Based on the data obtained it is known that the highest ability is in the representation of images with the average score of students in 3 different schools of 95.2% in the category of excellent.The average score of mathematical representation capability is 87.3% with a very good category. Keywords: Physics, Concepts, Multirepresentation Capabilities